Changes in left atrial function following two regimens of combined exercise training in patients with ischemic cardiomyopathy: a pilot study - Caminiti, Giuseppe; Volterrani, Maurizio; Iellamo, Ferdinando; Marazzi, Giuseppe; Manzi, Vincenzo; D’Antoni, Valentino; Vadalà, Sara; Di Biasio, Deborah; Catena, Matteo; Morsella, Valentina; Perrone, Marco Alfonso (Frontiers in Cardiovascular Medicine, 2024)
Purpose Left atrial dysfunction has shown to play a prognostic role in patients with ischemic cardiomyopathy (ICM) and is becoming a therapeutic target for pharmacological and non-pharmacological interventions. The effects of exercise training on the atrial function in patients with ICM have been poorly investigated. In the present study, we assessed the effects of a 12-week combined training (CT) program on the left atrial function in patients with ICM. Methods We enlisted a total of 45 clinically stable patients and randomly assigned them to one of the following three groups: 15 to a supervised CT with low-frequency sessions (twice per week) (CTLF); 15 to a supervised CT with high-frequency sessions (thrice per week) (CTHF); and 15 to a control group following contemporary preventive exercise guidelines at home. At baseline and 12 weeks, all patients underwent a symptom-limited exercise test and echocardiography. The training included aerobic continuous exercise and resistance exercise. The analysis of variance (ANOVA) was used to compare within- and inter-group changes. Results At 12 weeks, the CTLF and CTHF groups showed a similar increase in the duration of the ergometric test compared with the control (ANOVA p < 0.001). The peak atrial longitudinal strain significantly increased in the CTHF group, while it was unchanged in the CTLF and control groups (ANOVA p = 0.003). The peak atrial contraction strain presented a significant improvement in the CTHF group compared with the CTLF and control groups. The left ventricular global longitudinal strain significantly increased in both the CTHF and the CTLF groups compared with the control group (ANOVA p = 0.017). The systolic blood pressure decreased in the CTHF and CTLF groups, while it was unchanged in the control group. There were no side effects causing the discontinuation of the training. Conclusions We demonstrated that a CT program effectively improved atrial function in patients with ICM in a dose–effect manner. This result can help with programming exercise training in this population.